Emergence and development of Muslim liberal in Indonesia - Solihin, Sohirin Mohammad (2010)
The book reveals the emergence of liberal Islam in Indonesia by tracing the root of historical perspective. It emerged long before independence where secular Muslims made their efforts to expose their religious understanding in the community. It came out in the first part from secular group who tried to portray the religion from the use of Western angles. Liberal thought which was propagated by Muslim scholars who, to a large extent, have sufficient understanding toward the teaching of Islam but simply look at using the rational approach. They also tended to interpret certain religious text it using their own judgment, ignoring the rules and principles laid down by the authority of Muslim scholars. ...